1990
DOI: 10.1073/pnas.87.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hinge region on complement activation, C1q binding, and segmental flexibility in chimeric human immunoglobulins.

Abstract: We have characterized a series of genetically engineered chimeric human IgG3 and IgG4 anti-dansyl (DNS) antibodies with identical antibody-combining sites but different hinge region amino acid compositions to determine how the hinge region influences Fab fragment segmental flexibility, Clq binding, and complement activation. Our data support the correlation between "upper hinge" length and Fab segmental flexibility; moreover, we confirm that a hinge region is essential for Clq binding and complement activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(44 citation statements)
references
References 15 publications
1
42
0
1
Order By: Relevance
“…These mutations of CDP571 conferred upon both antibodies the ability to form disulfide bonds between heavy chains, given that only trace amounts of half-IgG molecules assembled into tetramers by noncovalent interactions were observed. A serine to proline substitution in the core hinge region of a chimeric mouse/human IgG4 (Angal et al, 1993) and the substitution of the hinge sequence in an IgG4 human antibody with that from a human IgG3 antibody (Tan et al, 1990) also resulted in a dramatic reduction of the amount of noncovalently associated half-lgG observed. In agreement with studies on a monoclonal human IgG4 (Virella & Parkhouse, 1973), the inter-heavy chain disulfide linkages of CDP571 were shown to be more sensitive to reduction than the heavy-light chain bridge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutations of CDP571 conferred upon both antibodies the ability to form disulfide bonds between heavy chains, given that only trace amounts of half-IgG molecules assembled into tetramers by noncovalent interactions were observed. A serine to proline substitution in the core hinge region of a chimeric mouse/human IgG4 (Angal et al, 1993) and the substitution of the hinge sequence in an IgG4 human antibody with that from a human IgG3 antibody (Tan et al, 1990) also resulted in a dramatic reduction of the amount of noncovalently associated half-lgG observed. In agreement with studies on a monoclonal human IgG4 (Virella & Parkhouse, 1973), the inter-heavy chain disulfide linkages of CDP571 were shown to be more sensitive to reduction than the heavy-light chain bridge.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with recombinant and recombinantlchimeric constructs of monoclonal antibodies have shown that antibodies bearing hinge regions of the y4 subclass (IgG4) are secreted as both disulfide bond-linked tetramers and as half-IgG 407 molecules assembled into tetramers by noncovalent interactions (Morrison et at.. 1988: Colcher et al. 1989: Tan et al. 1990: Canfield & Morrison, 1991: King et at.. 1992: Angal et al, 1993.…”
mentioning
confidence: 99%
“…The upper hinge region (DKTHT) of human IgG1 connects the Fab arms to the core segment and influences Fab-Fab flexibility; N-terminal residues from the upper hinge region are reported to interact with the C H1 domain. [17][18][19] The lower intact antibodies. 14,15 This flexibility enables IgG molecules to bind antigens of a variety of shapes and sizes and also allows the effector domain (Fc) to bind the Fc receptor or complement.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some reports have suggested that a reduction in the flexibility or length of the hinge region directly correlates with an increase in complement activation (2,(7)(8)(9)(10). Finally, other studies have indicated the lack of such a simple correlation (11)(12)(13). Likewise, the nature and properties of the hinge region also influence binding of the Fc to various Fc␥Rs as well as Ab-dependent cell-mediated cytotoxicity (ADCC) activity.…”
mentioning
confidence: 99%